Model Evaluasi Pembelajaran PAI Berbasis Daring Di MTs. Usman Syarif Medan Selama Pandemi Covid-19 - Lubis, Rahmat Rifai; Enita, Putri; Marpaung, M. Abdurrahman Fauzi; Harahap, Rediani (el Buhuth: Borneo Journal of Islamic Studies, 2020)
This study aims to analyze (1) evaluation model of online Islamic education based on cognitive aspects, (2) evaluation model of online Islamic education based on affective and spiritual aspects, and (3) evaluation model of online Islamic education based on psychomotor aspects. This research was conducted at MTs. Usman Syarif Medan, while the research method used in this study is a qualitative research method with a descriptive study approach. The data collection techniques used were interviews, observation, and documentation. The results showed that the online learning evaluation model of PAI based on the cognitive aspects was carried out with several forms of evaluation, namely questions in the form of multiple choice tests, questions in the form of essay tests, portfolios, and oral exams. The Affective and Spiritual Aspect Evaluation Model is in the form of projective assessment, objective assessment, attitude and spiritual assessment rubrics. The Psychomotor Aspect Learning Evaluation Model was carried out using a skills assessment rubric.